Yield and composition of grain sorghum stover - Vanderlip, R. L.; Schneider, L.R.; Bolsen, K.K. (Kansas State University. Agricultural Experiment Station, 2011)
Last year in Kansas approximately 3.8 million acres produced 243 million bushels of grain sorghum plus a large amount of forage left in the field as a potential source of feed for livestock. The objective of this report is to indicate the quantity of forage available after normal and early (high-moisture) harvest of sorghum grain.
Keywords: Beef; Grain sorghum; Forage; Yield